Design, Simulation and Analysis of a Microstrip Rampart Line Antenna (MRLA) for a MIMO-OFDM Transceiver Module in UAV Applications - Jeba Kumar RJS; G.P. Ramesh (Science & Technology Asia, 2025)
An Unmanned Aerial Vehicle (UAV) is a swarm of Mobile Sensor Networks that operates in the recommended standard of 802.11g, which needs a miniaturized Microstrip Rampart Line Antenna (MRLA) to establish full duplex Multiple-Input Multiple-Output (MIMO) Radio Frequency Communication. Hence, a MIMO Orthogonal Frequency-Division Multiplexing (OFDM) transceiver module which operates in 432.5 MHz for UAV application is in need for compact size antenna. The innovative aspect of this research paper is to showcase the novel rampart design, i.e., Microstrip Rampart Line Antenna (MRLA) and its practical evaluation, specifically operating within the Ultra-High-Frequency (UHF), i.e., 432.5 MHz. The novelty of the recommended design is to enhance performance in terms of both bandwidth and overall radiation properties. To attest the correctness of the proposed MRLA design, the simulation findings are compared with the state-of-art research design for size reduction comparison, fabricated results were observed, and thereby measured test results via fabrication were found in line with simulated results. The observed fabricated test results of the proposed MRLA antenna for MIMO-OFDM module, constructed for the Operating-Range-of-Frequency (f0) of 432.5 MHz, yields a Reflection Coefficient (S11) value of -47 dB, an acceptable VSWR numerical value of 1.5, and an Axial Ratio (AR) of 1.8; hence it is ideally suited to establish medium-to-long range UAV RF communication. This proposed antenna will pave the way for futuristic AI based Reconfigurable Antennas for advanced UAV applications.